Descending Mediastinitis with Mediastinal Abscess after Supracricoid Partial Laryngectomy. (June 2013) - Benito, José; Espinoza, Sophie; Gutiérrez-Fonseca, Raimundo; Bagan, Patrick; Laccourreye, Ollivier
We document a rare and not-yet-reported condition after supracricoid partial laryngectomy: The development of descending mediastinitis with mediastinal abscess. We present a case in which early diagnosis and team management allowed for a successful outcome. The pathophysiology of this severe complication, as well as its diagnosis, management, and prevention, is discussed, together with a review of the medical scientific literature.